Almost 50% of young alpine and mogul skiers who had ended their elite careers after high school reported this was due to injuries. Issue 6 (30th June 2022) - Abrahamson, Josefin; Jónasson, Pall; Sansone, Mikael; Aminoff, Anna Swärd; Todd, Carl; Karlsson, Jón; Baranto, Adad
Objectives: To evaluate activity level, sports career and injuries in young elite alpine and ogul skiers five years after High school graduation. Methods: All students (n=76) at Åre Ski Academy High school (National Sports High school) were invited to participate in this prospective study at baseline. Two skiers were excluded. They answered questions regarding type and frequency of training and symptoms/injuries in the back and/or hips. Five years after graduation the skiers were contacted, by phone, to answer the same questions with additional questions about the reason why they no longer were at the same level or had finished skiing. Results: Sixty (81%) skiers answered the 5-year follow-up. Totally, 44 skiers (73%) had ended their elite careers, in mean 1 year after graduation. Of those, 48% (21 skiers) reported injuries were the reason they were forced to quit. Ten had back injuries, 6 knee injuries, 3 concussions and two hip injuries. Conclusion: Almost 75% of young alpine and mogul skiers had ended their elite skiing careers, with 48% reported this was due to injuries from their skiing.